Defying the Odds: A Rare Case of Giant Recurrent Retroperitoneal Liposarcoma Managed Over Eight Years - Samir Gupta; NH Mallikarjun; Kaivalya R. Saoji; Akshi Raj; Tejus V. Nagireddy (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Retroperitoneal liposarcoma (RPLS) is a rare and challenging soft tissue sarcoma, comprising 15–20% of adult retroperitoneal tumors. Despite surgical resection, recurrence rates are high, and adjuvant therapies are limited. We present a unique case of a 42-year-old woman with recurrent RPLS, who experienced five recurrences and underwent four major surgeries over eight years. The most recent surgery involved removing a massive 13 kg, 40 × 25 × 17 cm tumor compressing adjacent organs. Histopathology consistently confirmed well-differentiated liposarcoma (WDLS), with one recurrence showing myxoid features. This case emphasizes the importance of aggressive surgical resection in managing recurrent RPLS, as well as vigilant long-term follow-up for early detection of recurrences. Despite significant morbidity from repeated surgeries, the patient showed remarkable recovery and long-term survival, highlighting the potential for favorable outcomes with individualized, multidisciplinary care. Our case, featuring long survival and multiple relapses, is unique, as only six cases with survival beyond six years have been reported in the past 12 years.